Effects of magnetic solidification on rod shaped Nd–Fe–Ti–Zr–Cr–B–C magnets with various diameters. (September 2013) - Wang, C; Lin, W C; Hsieh, C C; Chang, W C; Chang, H W; Sun, A C
Abstract : The bulk nanocrystalline Nd–Fe–B magnets in cylindrical form with various diameters were prepared by injection casting of the molten alloy into copper moulds. The effects of the diameter size and the application of magnetic field during the solidification process on the magnetic properties and microstructure of Nd9·5 Fe71·5 Ti2·5 Zr0·5 Cr1 B14·5 C0·5 alloy have been studied. The smaller the diameter is, the better magnetic properties can be obtained. The intrinsic coercivity of bulk magnet is more sensitive to the diameter size than the remanence. Applying a 3·0 kOe magnetic field during the casting process is helpful to refine the grain size, thus improving the magnetic properties of bulk magnets, especially the intrinsic coercivity. The increase in the intrinsic coercivity induced by the applied magnetic field is much obvious for the samples with larger size.